Trends and future projections of liver cancer attributable to metabolic dysfunction-associated steatohepatitis in China from 1990 to 2050 - Jincheng Tang; Renyi Yang; Kexiong Li; Wei Peng; Zuomei He; Wenhui Gao; Puhua Zeng (Scientific Reports)
Abstract Metabolic dysfunction-associated steatohepatitis (MASH)-induced liver cancer (MALC) is a global public health challenge. This study aims to analyze the epidemiological characteristics of MALC from 1990 to 2021 and project future trends up to 2050 in China. Data on MALC were obtained from the Global Burden of Disease Study (GBD) 2021, including incidence, deaths, and disability-adjusted life-years (DALYs). The burden of MALC in China and trends in age-standardized rate (ASR) were analyzed using estimated annual percentage changes (EAPCs). Additionally, the attributable risk factors for MALC-related deaths and DALYs in China were assessed, and Bayesian age-period-cohort models were used to predict trends in ASR up to 2050. Compared to 1990, the number of MALC incidence, deaths, and DALYs in China more than doubled by 2021. From 1990 to 2021, the age-standardized incidence rate (ASIR) [EAPC: 0.72; 95% confidence interval (CI) 0.52 to 0.92] and age-standardized mortality rate (ASMR) (EAPC: 0.33; 95% CI 0.13 to 0.53) of MALC showed an upward trend. The ASIR, ASMR, and age-standardized DALYs rate (ASDR) in males consistently exceeded those in females. In 2021, the burden of MALC incidence, deaths, and DALYs in China was predominantly concentrated in the 65–69 age group. Among the risk factors recorded in GBD 2021, age-standardized MALC mortality in China in 2021 was primarily attributable to high fasting plasma glucose and smoking. It was also found that the proportion of risk factors for MALC in China was similar to those in high-middle SDI regions and World Bank upper-middle-income regions. Furthermore, predictive models estimate that by 2050, the ASIR and ASMR of MALC in both male and female patients in China will show a declining trend. The burden of MALC in China exhibits age and gender disparities. Although its future burden is expected to improve, it remains a significant public health challenge in China. Targeted intervention strategies must be developed based on its epidemiological characteristics and risk factors to mitigate the burden of MALC in China.